Validation of Swarm accelerometer data by modelled nongravitational forces. Issue 10 (15th May 2017) - Bezděk, Aleš; Sebera, Josef; Klokočník, Jaroslav
Highlights: Validation of Swarm accelerometer data in all three instrument components. Linear temperature correction proposed, where temperature has a constant time shift. Correlation of accelerometer anomalous periods and signal variability demonstrated. Abstract: Swarm is a three-satellite mission of the European Space Agency, in orbit since November 2013, whose main objective is the study of the Earth's magnetic field from space. As part of other scientific payload, each Swarm satellite is equipped with an accelerometer that measures the nongravitational forces (e.g. atmospheric drag and radiation pressure). Since the mission beginning, the Swarm onboard accelerometer observations have been facing a problem of much higher temperature influence than it had been anticipated in the pre-launch tests. In our paper, we use the a posteriori computed models of physical nongravitational forces acting on each satellite for external validation of the accelerometer measurements. To reduce the high temperature dependence, we apply a simple and straightforward method of linear temperature correction. The most successful application of this approach is for the along-track component of the accelerometer data, where the signal magnitude is strongest. The best performing accelerometer is that of the Swarm C satellite, the accelerometer of Swarm A displays more temperature dependence and noise, the noisiest accelerometer data set is provided by Swarm B. We analyzed the occurrence of anomalous periods in the along-track accelerometer component of Swarm A and Swarm C, when the number of accelerometer hardware anomalies is peaking. Over the time interval from June 2014 to December 2015, we found a correlation between these anomalous periods and the minima in the time-varying part of the modelled nongravitational signal.